ANALISIS PRODUKTIVITAS DAN LUAS TANAMAN JERUK SIAM SAMBAS TAHUN 2015-2020 - Kiki Kristiandi; Rini Fertiasari; Nurul Fatimah Yunita; Theresia Widji Astuti; Dian Sari (Mimbar Agribisnis: Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2021)
Siam orange is a commodity of Sambas district and is one of the types of agriculture developed by the Sambas district government, besides that, Sambas district is a pilot area in the agricultural sector in West Kalimantan. The purpose of this study was to analyze the level of plant area and productivity of Siam oranges in 2015-2020. The research approach is a cross sectional study. This data is secondary data with a time series (time series) obtained from the Department of Agriculture and Food Security of Sambas Regency. In addition, this research is quantitative descriptive. The results showed that Tebas District is one of the areas that has a plant expansion rate among other districts, while productivity (kg/tree) is mostly found in Sebawi, Sambas, Jawai, South Jawai, Tebas, Semparuk, Salatiga, Teluk Keramat Districts. Tekarang, Selakau timur, Pemangkat and Selakau. Average productivity results. Siam orange ranges from 33 kg / tree. Increasing the number of plants and products in chayote in Sambas Regency is one of the business opportunities in the agricultural sector and agricultural products can be developed into other preparations such as food and non food.